1.

2.

**Solution:**
1)

Use factoring,

x^2(4x^2 - 18) = 0, using ZFT

x^2 = 0, that means a double root of zero, {0 ,0}and next is 4x^2 - 18 = 0,

for 4x^2 - 18 = 0
x^2 = 18/4

x1 = (3/2) sqrt 2

x2 = -(3/2) sqrt 2

x = {0, 0, (3/2) sqrt 2, x2 = -(3/2) sqrt 2}
- --------------------------------------------------------------------------------

2)

,

(3x + 1)^(1/3) = 5,

raise to 3 both sides

[(3x + 1)^(1/3)]^3 = [5]^3,

3x + 1 = 125, solving for x, we have

3x = 125 - 1,

3x = 124

x = 124/3 = 41.333333 . . . .

CHECK: (3(124/3) + 1)^1/3 - 5 = 0,

(124 + 1)^1/3 - 5 = 0

125^1/3 - 5 = 0

5 - 5 = 0

0 = 0, indeed

see graph